(untitled) (Global Journal of Science Frontier Research, 2025)
Improving the structural integrity of ships against collisions has received much attention due to the recent rise in maritime safety regulations, such as SOLAS (Safety of Life at Sea), and the increasing number of accidents involving displacement-type general cargo vessels. Collisions are a constant danger for ships like displacement-type general cargo vessels, which face the greatest number of accidents due to the presence of stationary objects or other vessels in high-traffic maritime zones. In collision analysis, the influence of engine mass on structural behavior during collisions is neglected in the literature. Finite element analysis (FEA) was utilized to simulate various collision scenarios, focusing on how engine mass and speed variations affect structural integrity in the case of the vessel colliding against a rigid wall. The study focuses on the modeling of a displacement ship made of 6061-T6 aluminum.